Beethoven im „Brockhaus“: Eine Spurensuche - Jacobshagen, Arnold (Die Musikforschung, 2021)
Full-length biographies about Ludwig van Beethoven were not published until after the composer's death. During his lifetime, biographical articles in dictionaries and encyclopaedias were therefore a particularly important source of information, since general encyclopaedias achieved a much wider circulation than specialist music publications. The first entry on Beethoven appeared as early as 1790 in Ernst Ludwig Gerber's Historisch-Biographisches Lexicon der Tonkünstler. The most widely read encyclopaedia for the educated middle class was the Conversations-Lexicon oder enzyklopädisches Handwörterbuch für gebildete Stände, first published by Brockhaus in 1809. This paper comparatively examines the articles on Beethoven from the first decades of the 19th century until the eleventh edition of 1863 and with regard to the emergence of typical narratives. It is noteworthy that the early entries on Beethoven, were shorter than those for other contemporary composers, contained false biographic information and were reluctant in their assessment of Beethoven’s oeuvre. This only changes after the composer’s death and raises the question whether, in the eyes of the general reading public, Beethoven really was the predominant musical figure in the first decades of the nineteenth century.